Taxing the Family – The Tax Unit: Should New Zealand Adopt a Family-Based Income Tax? - Hodgson, Helen (Thomson Brookers, 2008)
In April 2008, the New Zealand Government issued a government tax policy discussion document considering whether families should be able to access a form of income splitting through the New Zealand tax system. In Australia and New Zealand, as with most other OECD countries, the individual is the unit of taxation. In applying the principles of equity, families are entitled to certain benefits,currently delivered primarily through the welfare system. This results in a mismatch between the unit taken into account for tax and welfare. In this article, the author explores the concept of the tax unit. The article will review, first, the two main methods of joint taxation, being the accumulation method and the income splitting method, examining the equity and efficiency of each method. The article will then review the New Zealand proposal in the context of this analysis. Finally, some of the alternative methods of providing support for the family will be discussed.